THE IMPACT OF THE COVID-19 PANDEMIC ON THE TOURISM SECTOR (CASE STUDY: SIDOLUHUR COFFEE BUNKER EDUCATIONAL TOUR) - Maulidya Nur Aini; Budi Handoyo; Yuswanti Ariani Wirahayu; Tuti Mutia (Universitas Negeri Malang, 2023)
Abstract The global pandemic caused by the novel coronavirus (Covid-19) has had a profound impact on the economic sector, particularly in the tourism industry. This study aims to evaluate the effects of the pandemic and analyze communication strategies for the Sido Luhur Coffee Bunker Education attraction during the Covid-19 pandemic. The research employs a case study methodology, gathering data through a literature review, observation, documentation, and interviews with business stakeholders. The findings indicate that the Covid-19 pandemic led to a reduction in visitor numbers and a decline in revenue. To navigate the challenges posed by the pandemic, tourism managers implemented several marketing strategies. (1) The establishment of a tourist environment in accordance with the Sapta Pesona guidelines, (2) The enhancement of tourism facilities at the site, (3) The reduction of admission prices, (4) The avoidance of an increase in employee numbers, (5) The assurance of visitor safety during the pandemic through offline marketing, and (6) The utilization of online marketing.